Promoter Binding and Nuclear Retention Features of Zebrafish IRF Family Members in IFN Response - An, Li-Li; Zhao, Xiang; Gong, Xiu-Ying; Li, Yi-Lin; Qu, Zi-Ling; Sun, Hao-Yu; Guo, Wen-Hao; Dan, Cheng; Gui, Jian-Fang; Zhang, Yi-Bing (Frontiers in Immunology, 2022)
Interferon regulatory factors (IRFs) constitute a family of transcription factors that synchronize interferon (IFN) antiviral response through translocating to nucleus and binding to the promoters of IFN and IFN-stimulated genes (ISGs). Fish contain 11 IRF members; however, whether or how fish IRF family genes function in IFN response remains limited. Herein, we determine the regulatory roles of 11 zebrafish IRF family members in IFN response relevant to their subcellular localization and promoter binding. Zebrafish IRF family members display three patterns of constitutive localization, only in nucleus (IRF1/2/9/11), only in cytoplasm (IRF3/5/7), and largely in nucleus with small amounts in cytoplasm (IRF4b/6/8/10). DNA pull-down assays confirm that all zebrafish IRF proteins are capable to bind fish IFN promoters, albeit to various degrees, thus regulating IFN gene transcription as activators (IRF1/3/5/6/7/8/9/11) or repressors (IRF2/4b/10). Further characterization of distinct IFN gene activation reveals that IRF1/3/5/6/7/8/9/11 efficiently stimulate zebrafish IFN1 expression, and IRF1/7/11 are selectively responsible for zebrafish IFN3 expression. Two conserved basic residues within the helix α3 of DNA binding domains (DBDs) contribute to constitutive or inducible nuclear import for all zebrafish IRF family members and DNA binding for most members, thereby enabling them to function as transcription factors. Our results reveal a conserved and general mechanism that specifies zebrafish IRF family proteins to nuclear import and DNA binding, thereby regulating fish IFN response.